Peran Naposo Nauli Bulung dalam Meningkatkan Kesadaran Politik Generasi Muda di Desa Hutabargot Nauli, Kabupaten Mandailing Natal - Nasution, Nislah; Zulkarnaen, Zulkarnaen (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
Hutabargot Nauli Village in Mandailing Natal Regency is a community deeply rooted in local traditions, where the youth organization Naposo Nauli Bulung (NNB) plays a significant role in shaping the mindset and behavior of the younger generation. This study investigates the strategic role of NNB in fostering political awareness among youth, particularly in the context of declining participation in village forums and local electoral processes. Employing a qualitative method with a descriptive case study design, data were collected through interviews, direct observations, and document analysis, and validated using data triangulation. The findings reveal that NNB possesses considerable potential as an agent of political socialization by integrating cultural norms, informal education, and localized political discourse. However, several challenges hinder its effectiveness, including low levels of political literacy, limited access to political information, and internal organizational conflicts. These findings mirror national trends indicating a disconnect between political awareness and civic engagement among youth. The study concludes that enhancing digital political literacy and encouraging active participation in village decision-making forums are critical steps. NNB can thus emerge as a transformative force in empowering rural youth to engage more meaningfully in democratic processes.